Kiedy w starożytności rozpoczynała się starość? - Jurkiewicz, Jerzy (Vox Patrum, 2011)
When does man begin to be old: when he is sixty, sixty-five and perhaps seventy? Nothing is more uncertain than the beginning of the old age. Is man`s age the matter of his heart, brain, mood, or chronological time? In the ancient world, there was no clear understanding regarding the beginning of the old age. We have different classifications of the stages of human life, but there was no specified year, which would mark the old age. It was a year between 46 and 60 years of age. Today the age of 46 is not the beginning of the old age. In the ancient world, life was much shorter, so it is not surprising that 46 years old was regarded as the beginning of old age. There were two trends in ancient Greece and Rome. One represented by Plato and Cicero: older people are wise, experienced, worthy of reverence and respect. The second trend represented by Aristotle: older people are quarrelsome, greedy, cowardly. The life of old people was different. The rich lived very well, but in general the old age in ancient times was a difficult time.